Attitudes toward occupations for deaf youth in Sweden. - DeCaro JJ; Mudgett-DeCaro PA; Dowaliby F (American Annals of the Deaf, 2001)
The study investigated the expressed advice of parents, teachers, and Deaf community leaders regarding careers for deaf students in Sweden. The research was conducted: (a) in a country where consensus has been achieved on recognition and accommodation of the educational needs of deaf students; (b) in a city with a very high concentration of deaf individuals, a continuum of educational facilities, and support for deaf students ranging from preschool through college; and, (c) in a community with a strong and active deaf organization and parent organization. The authors found that, despite many advances in the country, communication in the language of the greater society is a potent factor in limiting occupational possibilities for the Deaf.